The Effect Of The Think Pair Share (TPS) Type Cooperative Learning Model On Students' Mathematical Problem-Solving Abilities In The Material Of Integer Numbers In Grade VII - Ruth Theofani Siagian; Efron Manik; Tutiarny Naibaho (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine whether the Think Pair Share (TPS) Cooperative Learning Model used in class VII influences students' mathematical problem-solving abilities in integer material. This study is a Quasi Experiment using cluster sampling techniques. The samples collected for this study were class VII-A as the experimental class, and class VII-B as the control class. The tool used was a test. The results of the calculation of mathematical problem-solving abilities showed that the Sig. (2-tailed) value was 0.000 <0.05 at a significance level of 5%. The average value for the experimental class' mathematical problem-solving abilities was 84.115, while the average value for the control class was 58.470. Then from the results of the N-Gain test, the average score for the experimental class was 0.84 (high criteria) and the control class score was 0.46 (medium criteria). So it can be concluded that the Think Pair Share (TPS) Cooperative Learning Model on Students' Mathematical Problem Solving Ability in Integer Material for Class VII SMP NEGERI 1 STABAT TA 2024/2025.